Case Report: Early Onset Systemic Lupus Erythematosus Due to Hereditary C1q Deficiency Treated With Fresh Frozen Plasma - Zecevic, Milica; Minic, Aleksandra; Pasic, Srdjan; Perovic, Vladimir; Prohászka, Zoltán (Frontiers in Pediatrics, 2021)
Background: hereditary C1q deficiency is associated with early-onset autoimmunity causing SLE or SLE-like disease as well as increased risk for infections with encapsulated bacteria. It is a rare genetic condition inherited in an autosomal recessive manner, caused by mutations in C1q genes. Treatment and management of this rare disease are very complex and include prophylactic vaccination, antibiotics, and immunosuppressive drugs. There are two possible modalities for the replacement of the missing protein: regular fresh frozen plasma (FFP) administration and allogeneic hematopoietic stem cell transplant because the protein is derived from monocytes. Replacing C1q with FFP is being attempted in some patients with success in controlling the disease and in avoiding flare. Case report: we report a case of sixteen-month-old girl with ulcerations in her mouth, skin erythema, and elevated liver enzymes. ANAs were positive, antibodies against dsDNA were negative, but she had positive anti-Smith antibodies. Complement complements C3 and C4 levels were normal. Total complement activity, classical pathway (hemolytic test) was deficient and C1q antigen was below the detection limit supporting the presence of C1q deficiency. The girl has pathogenic homozygous nonsense mutation in C1qC gene, Arg69Ter (c205>T). The initial response to corticosteroid therapy was good. Regular fresh frozen plasma infusions keep her disease under control, and we were able to reduce the dose of corticosteroids. Conclusion: young patients with cutaneous lesions resembling SLE, early onset of autoimmunity, with normal C3, C4, elevated ANAs, and negative anti-dsDNA, C1q deficiency should be suspected and complement screening tests should be done. It is important to exclude secondary C1q deficiency. FFP in our patient seems to be well tolerated, without any side effects, able to control the disease.